Cutaneotrichosporon (Trichosporon) debeurmannianum associated with a subcutaneous mycotic cyst successfully treated with voriconazole. (1st March 2020) - Noy, M. L.; Abdolrasouli, A.; Borman, A. M.; Fraser, M.; Francis, N.; Moore, L. S. P.; Merika, E. E.
Abstract: Click here for the corresponding questions to this CME article.